DEVELOPING SKILLS AND COMPETENCES IN THE FIELD OF SIMULTANEOUS TRANSLATION IN STUDENTS - Muhammadieva, Ugiloy (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
This article examines the process of skill and competence formation in simultaneous interpreting among university students. It explores pedagogical approaches, challenges encountered during training, and the development of key interpreter competencies such as listening comprehension, note-taking, short-term memory, and rendering accuracy. The study analyzes the effectiveness of various teaching methods and assesses the factors contributing to successful interpreter development, including individual aptitude, dedicated practice, and exposure to diverse interpreting contexts. The findings provide insights into effective strategies for fostering simultaneous interpreting skills and competencies in students, contributing to the field of interpreting pedagogy and training.